2018
DOI: 10.3390/en11102787
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes towards Industrial CO2 Capture and Storage Products and Technologies

Abstract: This paper discusses and elicits consumer attitudes towards industrial carbon dioxide (CO2) capture and storage (ICCS) products and technologies. It presents a comprehensive review of the relevant research literature on consumer attitudes towards ICCS represented by the willingness-to-pay (WTP) and willingness-to-accept (WTA) negative externalities and outcomes of the carbon capture and storage (the so-called “not-in-my-backyard” (NIMBY) approach). In addition, it employs a concise empirical model that uses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 60 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…A large proportion of WTP studies use either the contingent valuation method (CVM) [8,9,12,15,16,19,[25][26][27][28] or the choice experiment (CE) [1,11,17,21,[29][30][31] to determine the influence of various factors on WTP. These factors can be related to the consumer's characteristics, such as: age, income or education and to the product such as: share of renewables, source of renewables or local provider.…”
Section: Methodsmentioning
confidence: 99%
“…A large proportion of WTP studies use either the contingent valuation method (CVM) [8,9,12,15,16,19,[25][26][27][28] or the choice experiment (CE) [1,11,17,21,[29][30][31] to determine the influence of various factors on WTP. These factors can be related to the consumer's characteristics, such as: age, income or education and to the product such as: share of renewables, source of renewables or local provider.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, economists and sociologists can study such issues as willingness-to-pay for various energy-related projects, for example the industrial CO2 capture and storage products and technologies [21]. Other good examples might be the public acceptance of renewable energy sources [22], behavioural changes thanks to the deployment of smart meters that help to save energy in households [23], the new approaches to the Corporate Social Responsibility (CSR) with regard to the development of energy projects [24,25], or the perceived threats to urban energy networks [26].…”
Section: Energy Economics and Sociologymentioning
confidence: 99%
“…The research in this field conducted in South Korea showed that even if people give RES-related investments preferential treatment, they may protest the locating of renewable energy power plants in their neighborhood (Woo et al 2019). In order to estimate the support for actions in the field of limiting climate change, apart from the WTP for green energy, the willingness-to-pay and willingness-to-accept negative externalities and outcomes of the carbon capture and storage indicators are also being used (Kashintseva et al 2018).…”
Section: Wtp -A Definitionmentioning
confidence: 99%